Gender differences in math and reading: Performance, self-concept and expectations (2020)
Previous studies show gender differences in math and language performance, mainly in adolescents. In this study, we aim to evaluate gender differences in self-concept, subjective value, expectations and academic performance, to analyze the relationships between the variables, and to understand their role in explaining performance in language and mathematics. A total of 406 4th and 5th grade students from Colombia participated in this study. The results show that girls have higher performance expectations in mathematics and language, as well as higher performance in language than boys. No gender differences were found in self-concept and the subjective value of the task. Self-concept, performance expectations and age explained performance in both mathematics and language. We discuss the implications of these results for narrowing the gender gap in learning. Because this study is the first attempt to explore the relationships between expectations and task-value beliefs in language and mathematics in Hispanic primary school students based on the Expectancy-Value Model, more research is needed to support or refute our findings. © 2020 Fundación Universitaria Konrad Lorenz.